A NEW ERA OF INTERNATIONAL LEGAL COOPERATION BETWEEN THE REPUBLICS OF UZBEKISTAN AND TÜRKIYE (World Bulletin of Management and Law, 2024)
In this article, the author touched on the new stage of the formation of the contractual legal framework between the Republics of Uzbekistan and Türkiye. The content and essence of the international agreements between the Republics of Uzbekistan and Türkiye and their specific features have been systematically studied and scientifically and theoretically substantiated. The development of diplomatic relations and international legal cooperation between Uzbekistan and Türkiye was analyzed using special, logical, political, theological, systematic, and normative methods of interpretation.